Research progress on the correlation between estrogen and estrogen receptor on postmenopausal sarcopenia - Zhang, Chengmei; Feng, Xin; Zhang, Xue; Chen, Yu; Kong, Juan; Lou, Yan (Frontiers in Endocrinology, 2024)
Estrogen is a necessary sex steroid hormone, and its activity is not only limited to the reproductive organs but also affects other organs and tissues, including skeletal muscles.In postmenopausal women, a decrease in estrogen levels leads to endocrine and metabolic dysfunction, resulting in osteoporosis, metabolic syndrome, and a tendency towards decreased muscle mass and strength. A decline in skeletal muscle mass is usually associated with sarcopenia, a prevalent disease observed in vulnerable elderly individuals. Additionally, different levels of estrogen associated with menstrual periods may regulate exercise performance in women. Therefore, estrogen is considered to play a crucial role in skeletal muscle homeostasis and motor ability, although the exact mechanism remains unclear. This suggests that estrogen plays a beneficial role in the recovery process after muscle recession. Based on the relevant literature, this paper discusses the impact of estrogen on skeletal muscle diseases and provides a review of recent research progress. The aim is to elucidate the role of estrogen in the treatment of postmenopausal skeletal muscle diseases and to propose possible future research directions and key scientific issues that must be addressed urgently. In this article, we reviewed the role of estrogen in postmenopausal skeletal muscle and outlined the proposed molecular mechanisms.